2020
DOI: 10.1016/j.rmcr.2020.101159
|View full text |Cite
|
Sign up to set email alerts
|

Adverse reaction report and retrospective analysis of black hairy tongue caused by linezolid

Abstract: The adverse reaction of Black Hairy Tongue (BHT) caused by linezolid is rare. We reports a case of linezolid-induced BHT, and reviews relevant literatures at home and abroad. It aims to provide a safe and reasonable basis for clinical medication use. A 14-year-old adolescent with pneumonia caused by methicillin-resistant Staphylococcus aureus (MRSA) developed a rash and pruritus due to Vancomycin. Instead, the patient was given linezolid 600mg q12h in injection during hospitalization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In our study there is a true statistically significant correlation between smoking and the hairy tongue infection, smoking leads to estimated prevalence of 75% in hairy tongue patients. [16][17][18][19][20][21][22][23][24][25] In contrast to several studies linking hairy tongue with smoking , there are some articles that do not confirm such high rates, they reported that the casual smoking poses a slightly increased risk of having BHT compared to non-smokers (15% to 10% in men, 5.5% to 5.2% in women). As a result all studies believed that smoking was a predisposing factor to trigger excess production of keratin and discoloration of the keratin.26-29 Our results show a significant relationship between HT and excess consumption of black tea and coffee which was similar to that in Prabha's study.30 However, other studies confirmed such a relationship.…”
Section: Discussionmentioning
confidence: 84%
“…In our study there is a true statistically significant correlation between smoking and the hairy tongue infection, smoking leads to estimated prevalence of 75% in hairy tongue patients. [16][17][18][19][20][21][22][23][24][25] In contrast to several studies linking hairy tongue with smoking , there are some articles that do not confirm such high rates, they reported that the casual smoking poses a slightly increased risk of having BHT compared to non-smokers (15% to 10% in men, 5.5% to 5.2% in women). As a result all studies believed that smoking was a predisposing factor to trigger excess production of keratin and discoloration of the keratin.26-29 Our results show a significant relationship between HT and excess consumption of black tea and coffee which was similar to that in Prabha's study.30 However, other studies confirmed such a relationship.…”
Section: Discussionmentioning
confidence: 84%
“…15 Cases of linezolid-induced BHT commonly suffer from poor appetite and loss of taste. Tongue discoloration occurs in nearly two week or long-term use of linezolid and can be resolved 2-3 weeks after linezolid discontinuation, 6 but the BHT may recur after reintroduction of linezolid. 16 However, little is known about the alterations in oral bacteria on the black tongue and the correlation between these changes and the occurrence of the black tongue.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Black hairy tongue (BHT) is also a rare adverse effect associated with Linezolid. 6,7 BHT is characterized by pigmentation of the dorsal tongue which appears black, or green or yellow, and may be accompanied by hypertrophy of the filiform papillae. [8][9][10] The prevalence of black hairy tongue varies highly in the general population ranging from 0.6% to 11.3% and is significantly higher in males.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, a literature review from 2020 found that six out of 14 linezolid-induced BHT cases were pediatric cases; this suggests that linezolid-induced BHT occurs even in pediatric patients. 4 antibiotics were used in our patient, BHT usually occurs 10-15 days after administration. 4 Linezolid was therefore the most likely cause.…”
mentioning
confidence: 92%
“…4 antibiotics were used in our patient, BHT usually occurs 10-15 days after administration. 4 Linezolid was therefore the most likely cause. The exact mechanisms of BHT are unknown, though altered oral microbial flora and overgrowth of chromogenic microorganisms have been proposed as possible causes because some antibiotics have been known to cause BHT.…”
mentioning
confidence: 92%